Pakistan Textiles can Bounce Back Vigorously - Ali, Asif; Khan, Muhammad; Ishaq, Amir; Hussain, Arif; Rehman, Shams Ur; Khan, Imran Ali; Shah, Syed Fahad Ali (International Review of Management and Marketing, 2020)
The purpose of this research study is to identify and analyze the methods for increasing the market share of the Pakistan Textile industry in the world. This paper discusses the macro economic factors responsible for advancement and development of the textile industry in leading textile producing countries. The approaches adopted in this study are: firstly, developing a set of key success factors by studying the market leaders in the world i.e. China, India and USA; secondly, problems are being identified in the Pakistan Textile industry by comparing those key success factors with the situations in Pakistan. The problems found in Pakistan textile are further investigated and verified through primary research based on qualitative data. Finally, a set of recommendations is developed for the solution of problems found in Pakistan textile industry to increase its market share in the world. This paper proposes suggestions for solving problems found in Pakistan textile industry. Proper implementation of the guidelines given in this study greatly improves the chances of the Pakistan textile industry realizing its full potentials and ultimately increases its world market share. Keywords: Pakistan, Textile Industry, Key Success Factors, Market Share JEL Classification: L67 DOI: https://doi.org/10.32479/irmm.9377